2018
DOI: 10.1007/s00128-018-2375-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Metal Accumulation in Three Fish Species (Silurus asotus, Cyprinus carpio, and Carassius auratus auratus) from the Jinsha and Tuo Rivers Located Upstream of the Yangtze River, China

Abstract: The concentrations of lead, chromium, cadmium, arsenic, and mercury were analyzed in the muscle and liver (hepatopancreas) of three fish species (Silurus asotus, Cyprinus carpio, and Carassius auratus auratus) from the Jinsha and Tuo Rivers. The above mentioned metal concentrations in the muscles of the three fish species were below the permissible limits, indicating that these fishes are safe for human consumption. The concentration of mercury in the carnivorous fishes was higher than that in the omnivorous f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The pH has an important effect on muscle quality and directly affects the storage, WHC, and processability of meat. In general, grass carp post-mortem muscle pH values vary from 6.2 to 6.7 ( Li et al., 2013 ). The present study showed that the post-mortem muscle pH of grass carp in the SM group was 6.47 and increased to 6.51–6.59 in the BSFLM groups, which indicated that BSFLM could increase the muscle pH.…”
Section: Discussionmentioning
confidence: 99%
“…The pH has an important effect on muscle quality and directly affects the storage, WHC, and processability of meat. In general, grass carp post-mortem muscle pH values vary from 6.2 to 6.7 ( Li et al., 2013 ). The present study showed that the post-mortem muscle pH of grass carp in the SM group was 6.47 and increased to 6.51–6.59 in the BSFLM groups, which indicated that BSFLM could increase the muscle pH.…”
Section: Discussionmentioning
confidence: 99%
“…Carassius auratus , a term encompassing varieties like Goldfish , Fangzheng Carassius auratus , Pengze Carassius auratus , and Polyploid Carassius auratus , is a species with a wide range of varieties ( 1 , 2 ). It is a historically significant freshwater cultured fish in China and East Asia.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, a cascade of six large hydropower dams has been constructed and operated along the middle reaches of the Jinsha River, which modified hydrodynamic processes, increased river water table, and impacted riparian ecosystems within reservoirs (Li et al 2018b;Xia and Xu 2018;Xiong et al 2019). Previous studies have analyzed the variations of metal(loid)s in surface water, suspended particles, and riverbed sediments as well as the biological accumulation of fishes (e.g., Silurus asotus, Cyprinus carpio, Carassius auratus) in the Jinsha River (Teng et al 2011;Wu et al 2013;Li et al 2018c;Yuan et al 2019Yuan et al , 2021. It is clear that an investigation on the spatial distribution and solubilization characteristics of metal(loid)s in riparian soils within reservoirs is crucial to drinking water security along the middle Jinsha River.…”
Section: Introductionmentioning
confidence: 99%